Judges’ Freedom of Expression and the Reasonable Observer Test in International Soft Law : Relevant Documents, the Operationalization of the Test and the Scale of Expectations Placed on It - Wojtanowski, Mateusz (2022)
The paper aims to discuss the reasonable observer test as a tool for assessing judges’ expression. The argument begins by analyzing the relevant provisions of international soft law, as inscribed in the instruments developed and adopted by the CoE and the UN. Subsequently, an operationalization of the test is proposed by identifying the factors to be taken into account in the application of the test. In the following step, the expectations placed on the reasonable observer test are addressed, whereby the juriscentric (“strong”) and post-analytical (“weak”) positions are outlined. The former relies on Artur Kozak’s law-philosophical conception, and the latter is underpinned by the topography of juristic power developed by Paweł Jabłoński and Przemysław Kaczmarek. The paper makes the case for the post-analytical approach, which places rather modest expectations on the reasonable observer test and considers it instrumental in structuring the discussion, rather than yielding indisputably reliable conclusions.
Keywords: freedom of expression; reasonable observer; judge; soft law; hard cases